Explaining Cyberloafing Behavior: The Role of General Strain Theory - Riza Bahtiar Sulistyan; Emmy Ermawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The internet has changed the way employees get things done. However, many have not been on target regarding the use of the internet among employees. The availability of internet facilities in many organizations is used for personal gain or what is often referred to as cyberloafing behavior. General strain theory in this research is used to explain cyberloafing behavior. This behavior is not a criminal act but violates organizational regulations caused by organizational support and employee work stress. This study aims to assess the role of organizational support and reduce employee stress levels and cyberloafing behavior. The method used is in the form of PLS ​​by involving 330 government employees in Lumajang Regency as a sample. The results showed that the organizational support felt by employees was able to reduce work stress. Employees who feel work stress will tend to behave cyberloafing. The existence of high organizational support has increased employee cyberloafing behavior. The higher the perceived organizational support, the lower the level of employee work stress, and cyberloafing behavior. An important finding in this study is that the general strain theory has been able to prove the existence of cyberloafing behavior caused by organizational support and employee work stress.